2021
DOI: 10.2147/cia.s306463
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Cemented Femoral Revisions for Periprosthetic Femoral Fractures in the Elderly: Comparison with Cementless Stems

Abstract: Introduction:The present study compares the outcome of the long cemented stem and the revision uncemented stem used in periprosthetic femoral fractures. We propose that the revision with a long stem cemented prosthesis does not compromise fracture healing. Patients and Methods: A consecutive series of 37 patients, operated between 2010 and 2017, were enrolled in a retrospective analysis. A long cemented stem was implanted in 21 patients (study group; age at operation: 63 to 89 years). A distally tapered fluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The available literature regarding optimal fixation comparing long cemented femoral stems and distally tapered uncemented stems in PPFs is very scarce. Most of these studies are limited by (retrospective) design and number of inclusions ( 10 - 11 , 14 - 15 ). One registry-based study with data from the Swedish Hip Arthroplasty Register compared the outcomes of cemented and cementless fixation for Vancouver B2 and B3 periprosthetic fractures ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available literature regarding optimal fixation comparing long cemented femoral stems and distally tapered uncemented stems in PPFs is very scarce. Most of these studies are limited by (retrospective) design and number of inclusions ( 10 - 11 , 14 - 15 ). One registry-based study with data from the Swedish Hip Arthroplasty Register compared the outcomes of cemented and cementless fixation for Vancouver B2 and B3 periprosthetic fractures ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…They reported no differences in risk of revision among cemented, cementless monoblock, and cementless modular revision components for the treatment of type B2 and B3 fractures, which is in line with our results. A recent study compared the outcome of long cemented stems and uncemented revision stems used in PPFs ( 10 ). Although early surgical complications were reported in both groups, an increased morbidity and complication rate was seen in the long-stemmed cemented group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical increment of primary THAs also results in the increment of revision operations in elderly patients due to trauma. Sponer et al 12) reported on the outcomes of revision arthroplasties in a comparison of cemented stems and cementless stems. According to the authors, use of a long stem cemented stem implant would provide a greater possibility of pain-free weight-bearing without compromising the process for healing fractures of osteoporotic bones associated with old age 12) .…”
Section: Outcomes Regarding Cementation For Ppf Of Primary Hip Arthro...mentioning
confidence: 99%